Qualitative consumer & marketing research - Belk, Russell W. (SAGE, 2013)
"Written for students, scholars, and marketing research practitioners by three qualitative marketing research pioneers, this book takes readers through the basics to an advanced understanding of the state of the art in qualitative marketing and consumer research. The book offers readers a practical guide to planning, conducting, analyzing, and writing-up research or editing multi-media presentations using both time-tested and new methods, skills, and technologies. With hands-on exercises that researchers can practice and apply, the book leads readers step-by-step through developing qualitative researching skills in creative data collection, analysis, and presentation, using illustrations drawn from the best of recent and classic research. Whatever your background, this book will help you become a better researcher and help your research come alive for others."--Publisher's website.